San Jose State University 1990 - Chicano Graduation, Keynote by Ron Gonzalez - Castellano, Alcario:::creator:::::::::::: (2022)
Video and transcripts of the 20th Anniversary of the establishment of the Chicano Commencement ceremonies at San Jose State University.